Role of Silicon Counteracting Cadmium Toxicity in Alfalfa (Medicago sativa L.) - Kabir, Ahmad H.; Hossain, Mohammad M.; Khatun, Most A.; Mandal, Abul; Haider, Syed A. (Frontiers in Plant Science, 2016)
Cadmium (Cd) is one of the most phytotoxic elements causing an agricultural problem and human health hazards. This work investigates whether and how silicon (Si) ameliorates Cd toxicity in Alfalfa. The addition of Si in Cd-stressed plants caused significant improvement in morpho-physiological features as well as total protein and membrane stability, indicating that Si does have critical roles in Cd detoxification in Alfalfa. Furthermore, Si supplementation in Cd-stressed plants showed a significant decrease in Cd and Fe concentrations in both roots and shoots compared with Cd-stressed plants, revealing that Si-mediated tolerance to Cd stress is associated with Cd inhibition in Alfalfa. Results also showed no significant changes in the expression of two metal chelators [MsPCS1 (phytochelatin synthase) and MsMT2 (metallothionein)] and PC (phytochelatin) accumulation, indicating that there may be no metal sequestration or change in metal sequestration following Si application under Cd stress in Alfalfa. We further performed a targeted study on the effect of Si on Fe uptake mechanisms. We observed the consistent reduction in Fe reductase activity, expression of Fe-related genes [MsIRT1 (Fe transporter), MsNramp1 (metal transporter) and OsFRO1 (ferric chelate reductase] and Fe chelators (citrate and malate) by Si application to Cd stress in roots of Alfalfa. These results support that limiting Fe uptake through the down-regulation of Fe acquisition mechanisms confers Si-mediated alleviation of Cd toxicity in Alfalfa. Finally, an increase of catalase, ascorbate peroxidase, and superoxide dismutase activities along with elevated methionine and proline subjected to Si application might play roles, at least in part, to reduce H2O2 and to provide antioxidant defense against Cd stress in Alfalfa. The study shows evidence of the effect of Si on alleviating Cd toxicity in Alfalfa and can be further extended for phytoremediation of Cd toxicity in plants.